2017
DOI: 10.5114/wo.2017.68623
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vitamin D receptor and vitamin D status in patients with oral neoplasms and effect of vitamin D supplementation on quality of life in advanced cancer treatment

Abstract: Aim of the studyVitamin D receptor (VDR) expression and serum vitamin D scores in oral premalignant lesions and oral cancer have not been widely analyzed. The role of vitamin D supplementation in advanced oral cancer for improving quality of life (QOL) is also a matter of research.Material and methodsVitamin D receptor expression and vitamin D scores were analyzed in normal oral mucosa (n = 95), leukoplakia (n = 23) and oral cancer (n = 87). 45 patients with advanced oral cancer subjected to chemoradiation wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 45 publications
1
54
0
9
Order By: Relevance
“…In the present study, we focused on the estimation of serum vita- what was previously reported by other authors (Anand et al, 2017;Bochen et al, 2018 andGrimm et al, 2015). Grimm et al (2015) reported that among the 42 OSCC patients in their study in a Cauca- et al, 2013).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In the present study, we focused on the estimation of serum vita- what was previously reported by other authors (Anand et al, 2017;Bochen et al, 2018 andGrimm et al, 2015). Grimm et al (2015) reported that among the 42 OSCC patients in their study in a Cauca- et al, 2013).…”
Section: Discussionmentioning
confidence: 66%
“…As for OSCC, Osafi et al (2014) via an in vitro study opined that the activation of two apoptotic pathways (caspase and bcl:bax) by vitamin D may be responsible for its anti-OSCC effects. The importance of vitamin D in cancer management has been previously investigated (Anand et al, 2017;Bochen et al, 2018). In patients with advanced cancers, it has been shown that vitamin supplementation reduced therapy-related toxicities and improved the overall quality of life of the patients (Anand et al, 2017;Bochen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…9 Safety of Vit D supplementation in pediatric cases prior to hematopoietic cell transplantation have also been reported. 22 Data from a study by Anand et al 23 with adult oral cancer patients revealed that Vit D supplementation significantly improved treatment associated mucositis. Another study with smaller patient cohort size (n=14) found no significant benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Недостатність вітаміну D і його рецепторів завжди виявляють при хворобі Альцгеймера та Паркінсона [29,47]. Описали 16 різних видів злоякісних пухлин, розвиток яких корелює з низькою інсоляцією, а їхня поширеність підвищується при дефіциті вітаміну D [8]. Оскільки рецептори до вітаміну D знаходяться в скелетних м'язах, то дефіцит може призводити до слабкості проксимальних м'язів і виникнення артриту [20].…”
Section: мета роботиunclassified
“…Дослідження Спіндера і Ескоти (2014) показали, що дефіцит вітаміну D у ВІЛ-позитивних пацієнтів підвищує ризик перорального кандидозу [16]. Недостатність і дефіцит «сонячного вітаміну» виявили в пацієнтів зі злоякісними пухлинами ротової порожнини, а фізіологічні концентрації вітаміну D відіграють певну роль у процесі їх лікування [8]. Останні наукові праці в галузі зубної імплантології довели вплив вітаміну D, імобілізованого на титанових імплантах, на індуковане формування кістки навколо останніх [30,36].…”
Section: мета роботиunclassified